2008
DOI: 10.1002/rra.1143
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic resistance of some selected vegetation in open channel Flows

Abstract: Vegetation in rivers has important roles in improving and restoring river environment. Other than it adds high aesthetic value to revetments, that it can be used as a levee protection in environmental friendly way. In open channel hydraulics, vegetation often causes changes in the flow resistance, usually resulting in the increase of flood stage. Both experimental and numerical researches have been conducted on flow resistance of vegetation in open channels, however, the researches were based mostly on the veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 14 publications
5
33
0
Order By: Relevance
“…In this case, previous study by Stagge [9] has claimed that at high-flow depths, water is not slowed by grass in the swale but allowing sedimentation and too high to undergo filtration. The results from Table 1 were also found similar to the previous study by Rhee et al [15], where when the flow depth is greater than the grass height, the submergence will occur and the roughness started to increase as the velocity increased. These findings have explained why the flow discharges in this study did not decrease as the swale bed gets rougher.…”
Section: Contributing Factorssupporting
confidence: 89%
“…In this case, previous study by Stagge [9] has claimed that at high-flow depths, water is not slowed by grass in the swale but allowing sedimentation and too high to undergo filtration. The results from Table 1 were also found similar to the previous study by Rhee et al [15], where when the flow depth is greater than the grass height, the submergence will occur and the roughness started to increase as the velocity increased. These findings have explained why the flow discharges in this study did not decrease as the swale bed gets rougher.…”
Section: Contributing Factorssupporting
confidence: 89%
“…(1) In traditional flume experiments, Rhee et al [30] determined a roughness coefficient that was 0.029-0.195 using the combination of flume and real grass. Research made by Abood et al [31] suggested that roughness coefficient was 0.01~0.23, and that roughness coefficient turned to the largest at a minimum water velocity or water depth.…”
Section: Discussionmentioning
confidence: 99%
“…4). Moreover, a high level of rhizome biomass was observed in the slope of raised fields because of the requirement of extensive root systems to keep P. australis growing normally (Rhee et al, 2008).…”
Section: Spatial Changes Of Rhizomes Of P Australismentioning
confidence: 99%